Research note: Does roughage and diluted feed have a health effect on Hubbard M77 broiler breeder cockerels? - Kathe E. Kittelsen; Guro Vasdal; Randi O. Moe; Franciska S. Steinhoff; Fernanda M. Tahamtani (Poultry Science)
Quantitative feed restriction during rearing of broiler breeders is a well-known welfare challenge. This is necessary to secure health and reproductivity in the adult birds, but is associated with hunger and frustration. One alternative to quantitative restriction is to dilute the feed and/or provide roughage. This allows the birds a larger ration of feed, where the aim is a better satiety and thereby less hunger and frustration. Diluted feed and roughage have been tested in breeder pullets in several studies, but only one time with cockerels (Ross 308) and never with M77, the male breeder line for the medium slow growing Hubbard JA787. The aim of this study was to investigate the effects of feed dilution and roughage on selected health indicators in broiler breeder cockerels, 5 to 10 wk of age (WOA). In total, 200 M77 cockerels were housed in 12 pens (6 pens/treatment), 16 to 17 birds per pen. The treatments were standard feed (Control), and feed diluted with (20 %) oat hulls and 150 g of roughage (lucerne alfalfa) daily per pen (D + R). The D + R birds received 20 % more feed per day. Body weight, pecking injuries and footpad dermatitis (FPD) were recorded weekly between 5 and 9 WOA. At 10 WOA all birds were euthanized and subjected to postmortem assessment. The results showed that the D+R birds were slightly heavier than the control group in the last two weeks of the trial (P = 0.02). This coincides with a marginally heavier gizzard and longer intestinal tract in the D+R group. The footpad scores were overall low in both groups and all ages, but with slightly more variation in the D+R group. Overall, the results showed few positive nor negative effects of diluted feed and roughage on the selected health parameters in M77 cockerels. Further studies are needed to explore this area more.